ELECTRONIC STRUCTURE OF GERMANIUM AND MN-BASED NANOWIRES AND NANOWIRES (American Journal of Interdisciplinary Research and Development, 2024)
The Lorentzian and spin-scattering components of magnetoresistance were found and distinguished in Ge: Mn thin films. The suppression of microwave magnetoresistance by the limitation of the dimensionality of Ge nanowires doped with Mn has been revealed. Spin-wave resonance in the long-ordered magnetic state and ferromagnetic resonance in Ge Mn clusters have been detected.